Poster 210: Effects of a Comprehensive Behavioral Health Program on Functional Outcomes after Osteochondral Allograft Transplantation in the Knee. Issue 7 (30th July 2022) - Williams, Jonathan; Rucinski, Kylee; Stucky, Renee; Nuelle, Clayton; Stannard, James; Cook, James
Objectives: To use prospectively collected registry data to evaluate an evidence-based shift in practice for implementation of a comprehensive behavioral health program, including preoperative screening and education in conjunction with postoperative counseling for their effects on patient-reported mental health scores and functional outcomes after osteochondral allograft (OCA) transplantation in the knee. We hypothesized that patient-reported preoperative mental health issues would be associated with inferior outcomes and that the comprehensive behavioral health program led by a health behavior psychologist would be associated with superior outcomes for these patients. Methods: With IRB approval and informed consent, patients undergoing transplantation in the knee were enrolled in a lifelong registry designed to collect comprehensive outcomes data. Patients that had large (>4cm 2 ) shell-graft OCA transplants and complete one-year data for patient-reported IKDC subjective knee evaluation, VAS Pain, SANE, PROMIS Physical Function, and PROMIS Mental Health measures for pre-operative and 1-year time points were included in analyses. One-year improvement (D) scores for each variable were calculated as the difference between each score compared to the respective pre-operative score. Patients who required OCA revision surgery or total knee arthroplasty within the study period were defined as graft failures. Patients treated after the shift in practice were assigned to the Psych cohort. Patients who self-reported a history of mental health issues (Anxiety, Depression, Bipolar, ADHD, Schizophrenia) were assigned to the Mental Health Issue (MHI) cohort. Patients whose mental health history could not be obtained were not included in the respective analyses. Two-tailed t-Tests were used to analyze the survey scores between cohorts. Chi-square tests were used to compare proportions of successful versus failed outcomes between cohorts. A p value < 0.05 was used to indicate statistical significance for all tests. Results: A total of 269 patients met criteria for inclusion in the Psych analysis and 189 patients met criteria for inclusion in the MHI analysis. One-year SANE raw scores (p=0.03), one-year Physical Function D scores (p<0.0001), one-year IKDC D scores (p<0.0001), and one-year Pain D scores (p=0.01) were significantly better for patients in the comprehensive behavioral health program cohort. One-year PROMIS Mental Health D scores (p<0.0001), one-year Physical Function raw scores (p=0.03), and one-year Physical Function D scores (p<0.0001) were significantly better for patients who did not have a history of mental health issues, while one-year SANE D scores (p<0.0001) were significantly better in the MHI cohort. A significantly higher proportion of patients in the comprehensive behavioral health program cohort had successful 1-year outcomes (87.5 versus 64%, p=0.037). No statistically significant difference in proportions of successful versus failed grafts was noted between patient cohorts with self-reported preoperative mental health issues compared to those without self-reported preoperative mental health issues (p=0.23). Conclusions: The results of this study highlight the potential impacts of mental and behavioral health on outcomes after osteochondral allograft transplantation surgeries in the knee. Improvements in pain, knee function, and overall physical function were significantly better in patients enrolled in a comprehensive behavioral health program prior to surgery, while patients with self-reported preoperative mental health issues including anxiety, depression, bipolar disorder, ADHD, or schizophrenia had significantly worse outcomes with respect to mental health, physical function, and knee function. In addition, graft failure rate as defined by the need for OCA revision or TKA was significantly lower (12.5%) for patients undergoing comprehensive preoperative behavioral health screening and education. Taken together, these data suggest that mental and behavioral health can have significant influences on clinical outcomes after OCA transplantation in the knee and that preoperative assessment and education in conjunction with postoperative counseling and support may result in more successful outcomes for patients. However, based on the multifactorial nature of outcomes in these complex cases, longer term outcome studies in a larger population of patients are required before conclusions regarding the direct impact of this shift in practice can be made.